2015
DOI: 10.1590/1807-3107bor-2015.vol29.0031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Treponemaspp. in endodontic retreatment-resistant periapical lesions

Abstract: This study investigated the presence of the Treponema species in longstanding endodontic retreatment-resistant lesions of teeth with apical periodontitis, the association of this species with clinical/radiographic features, and the association among the different target species. Microbial samples of apical lesions were collected from twenty-five adult patients referred to endodontic surgery after unsuccessful root canal retreatment. Nested-PCR and conventional PCR were used for Treponema detection. Twenty-thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Studies also found that Spirochaetes exist in the oral cavity and were correlated with oral disease, e.g., the increased severity of marginal bone loss during bone healing around the non-submerged implant was related to an increased abundance of species in the phylum Spirochaeta [24]. Treponema denticola, Treponema pectinovorum, and Treponema socranskii were correlated with inflammatory periodontal diseases [25,26]. There has been no previous study reporting Spirochaetes in nasal mucosal inflammatory disease, and Spirochaeta abundance was very low in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that Spirochaetes exist in the oral cavity and were correlated with oral disease, e.g., the increased severity of marginal bone loss during bone healing around the non-submerged implant was related to an increased abundance of species in the phylum Spirochaeta [24]. Treponema denticola, Treponema pectinovorum, and Treponema socranskii were correlated with inflammatory periodontal diseases [25,26]. There has been no previous study reporting Spirochaetes in nasal mucosal inflammatory disease, and Spirochaeta abundance was very low in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting failure in endodontic treatment have revealed that different microorganisms can be found in the main root canal, lateral canals, dentinal tubules and in a few cases can extend to the perirradicular tissues (20)(21)(22). Even when non-surgical retreatment procedures are adequately performed, failure can happen (23).…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus gordonii has been shown to be an important player in the development of periodontitis as it is involved in co-adhesion and metabolic interactions with other pathogens (53,57). Treponema socranskii has been associated with peri-implant diseases (58,59), lesions of teeth with apical periodontitis (60), infected root canals and abscesses (61). Veillonella dispar is an earlier biofilm colonizer (62) and involved in periodontal disease (63).…”
Section: Discussionmentioning
confidence: 99%